2011
DOI: 10.1037/a0022028
|View full text |Cite
|
Sign up to set email alerts
|

Numeracy and Medicare Part D: The importance of choice and literacy for numbers in optimizing decision making for Medicare's prescription drug program.

Abstract: Studies on decision making have come to challenge the idea that having more choice is necessarily better. The Medicare prescription drug program (Part D) has been designed to maximize choice for the consumer but has simultaneously created a highly complex decision task with dozens of options. In this study, in a sample of 121 adults, we examined the impact that increasing choice options has on decision-making abilities in older versus younger adults. Consistent with our hypotheses, we found that participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 49 publications
5
82
0
Order By: Relevance
“…Furthermore, in the decision-making and cognitive aging literature, researchers have shown that strategies such as presenting less information (i.e., reducing cognitive load) when making complex decisions can effectively increase older adults' decision-making capabilities (e.g., medical decision, Wood et al, 2011). Finally, although there has been limited success in reducing HB by educating individuals on the bias (Fischhoff, 1982), developing awareness of the bias is essential so that protective mechanisms can be implemented.…”
Section: The Implications Of Hindsight Bias In Older Adultsmentioning
confidence: 99%
“…Furthermore, in the decision-making and cognitive aging literature, researchers have shown that strategies such as presenting less information (i.e., reducing cognitive load) when making complex decisions can effectively increase older adults' decision-making capabilities (e.g., medical decision, Wood et al, 2011). Finally, although there has been limited success in reducing HB by educating individuals on the bias (Fischhoff, 1982), developing awareness of the bias is essential so that protective mechanisms can be implemented.…”
Section: The Implications Of Hindsight Bias In Older Adultsmentioning
confidence: 99%
“…Recent systematic reviews have demonstrated that low health literacy test scores are associated with numerous adverse health outcomes and poor use of health care services (Berkman, Sheridan, Donahue, Halpern, Viera, et al, 2011;. Likewise, numeracy skills have been implicated in the ability to benefit from health care (Galesic & Garcia-Retamero, 2011;Wood et al, 2011). In order to lift literacy-related barriers to health, enhancing patients' health literacy and numeracy (Baur & Ostrove, 2011;Galesic & Garcia-Retamero, 2011;Rudd, Soricone, Santos, Zobel, & Smith, 2005) and adjusting services to low literacy levels (Rudd, 2010) have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Absent actionable plan information, choices may be informed by brand recognition, word of mouth, or other sources. [7][8][9] When information is available, interpreting numerous complex options is challenging; [10][11][12][13][14][15] beneficiaries may not be equipped to weigh the worth of attributes, including quality.…”
Section: Introductionmentioning
confidence: 99%